Analisis Hubungan Intensitas Bangunan (KLB Maksimum) dan Kapasitas Jalan dalam Menentukan Tingkat Kinerja Jalan - Fadil Achsan; Muhammad Yamin Jinca; Arifuddin Akil (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2022)
One of the factors that influence building intensity is the Building Floor Coefficient (BFC). Makassar City Spatial Planning 2015-2034 has set the Maximum BFC value, including on the Jalan Sultan Alauddin corridor. However, based on interlocutors with the specified agency, in the regulation, the BFC value has not taken into account aspects of road capacity. This study aims to evaluate the provisions of the BAC stipulated in the Jalan Sultan Alauddin corridor and formulate appropriate directions to increase the level of road service so that the building intensity is in accordance with the available road capacity. This research was conducted from January to July 2021 (7 months). The research method uses a supply and demand analysis approach. The supply approach focuses on road capacity as the object of research. Meanwhile, the demand approach focuses on building intensity limits to see how much the trip pull is. The results of the analysis show that the maximum BFC provision on the Jalan Sultan Alauddin corridor is too high and does not match the road capacity. The maximum traffic volume (Volume Capacity Ratio/VCR) obtained from the simulation results exceeds the road capacity on one of the segments with a VCR value of 1.00. Meanwhile, the tolerance limit for the VCR value on Jalan Sultan Alauddin, which is a primary arterial road, is 0.70. The direction of the recommendations proposed is to reduce the value of BFC and/or road capacity management.